PERKEMBANGAN MOTORIK HALUS ANAK USIA 5 TAHUN YANG MENGIKUTI PAUD DI KECAMATAN CURUP - Marsofely, Reka Lagora; Eliana, Yuniarti, (Politeknik Kesehatan Kemenkes Bengkulu, 2017)
Motor skills children need to be developed for the child's body has not been a lot of skills that will collide with the newly learned skills. ECD is a development effort that is aimed at children from birth up to the age of six years, which is done through the provision of educational stimulation to assist the growth and development. Based on data from the Department of Health Rejang Lebong in 2015, only (13.2%) were followed early childhood. The purpose of research to know knowledgeable picture fine motor development of children who attend early childhood education in the District Curup. The study design used is descriptive research design, sampling technique is purposive sampling, data collection is done by using a tool such as assessment sheets DDST II, research was conducted in March and April 2016. Place in early childhood studies conducted in the District Curup. The results obtained by univariate analysis study conducted by researchers of the 52 respondents in the working area of ​​the District toddlers Curup 2016 found that 49 (94.23%) of the children passed the test fine motor development DDST II, 3 (5.77%) children failed during the tests DDST II fine motor development. It is expected to parents to educate children at an early age so that the child's fine motor development is not compromised.